Structure and mutation of deoxypodophyllotoxin synthase (DPS) from Podophyllum hexandrum - Ingold, Zoe; Grogan, Gideon; Lichman, Benjamin R. (Frontiers in Catalysis, 2023)
Deoxypodophyllotoxin synthase (DPS) is a 2-oxoglutarate (2-OG) dependent non-heme iron(II) dioxygenase that catalyzes the stereoselective ring-closing carbon-carbon bond formation of deoxypodophyllotoxin from the aryllignan (-)-yatein. Deoxypodophyllotoxin is a precursor of topoisomerase II inhibitors, which are on the World Health Organization’s list of essential medicines. Previous work has shown that DPS can accept a range of substrates, indicating it has potential in biocatalytic processes for the formation of diverse polycyclic aryllignans. Recent X-ray structures of the enzyme reveal possible roles for amino acid side chains in substrate recognition and mechanism, although a mutational analysis of DPS was not performed. Here, we present a structure of DPS at an improved resolution of 1.41 A, in complex with the buffer molecule, Tris, coordinated to the active site iron atom. The structure has informed a mutational analysis of DPS, which suggests a role for a D224-K187 salt bridge in maintaining substrate interactions and a catalytic role for H165, perhaps as the base for the proton abstraction at the final rearomatisation step. This work improves our understanding of specific residues’ contributions to the DPS mechanism and can inform future engineering of the enzyme mechanism and substrate scope for the development of a versatile biocatalyst.